PENERAPAN WEBSITE BERBASIS CUSTOMER RELATIONSHIP MANAGEMENT UNTUK MENDUKUNG SISTEM INFORMASI - Ida Darwati (Paradigma, 2010)
Today's business competition is getting tight, making the company must have a strategy to retain customer loyalty. One strategy is the implementation of web-based Customer Relationship Management (CRM), which is intended to support information systems. Web based CRM is designed to add new customers and create customer loyalty expected good relations between companies and customers are always creating and improving corporate profits and add value to the company. keyword:web-based apllication CRM, information system